Implementasi Metode Nine Tools untuk Meningkatkan Kualitas Produk Nakas di CV Indah Karya Furniture - Shodiqin, Ezza Afdlol Maulana; Sulistyawati, Dwi Retna; Zulfa, Muhammad Choiru (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
CV. Indah Karya Furniture, a company engaged in the furniture manufacturing industry, faces challenges in maintaining the quality of its flagship product, the meja nakas (nightstand). This research employs the Nine Tools approach, a combination of the basic seven tools and the new seven tools, including: control chart u, stratification, Pareto diagram, histogram, scatter diagram, fishbone diagram, affinity diagram, interrelationship diagram, and tree diagram. The data analyzed consists of production and defect data from July 2024, totaling 355 units. The findings reveal that delamination is the most frequent defect, with 101 occurrences (70%), followed by uneven surfaces with 28 occurrences (19%), and joint gaps with 16 occurrences (11%). According to the u control chart, the production process is statistically unstable, as some points exceed the upper control limit. The scatter diagram indicates a random relationship between production volume and defect count.